2019
DOI: 10.1002/ente.201900066
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Manganese Cobalt Phosphide with Yolk–Shell Structure for Overall Water Splitting

Abstract: The development of low‐cost, earth‐abundant, and efficient catalysts for overall water splitting, involving the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), attracts tremendous attention in recent years. Herein, this work reports the preparation of Mn‐Co phosphide (Mn‐Co‐P) bifunctional catalysts with a yolk–shell structure by a facile hydrothermal route. The as‐prepared catalysts exhibit an excellent catalytic activity with the low overpotentials of 66 mV at 10 mA cm−2 for HER and 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…39,45 The broad peak at 134.0 eV is due to the oxidized P species. 46 The peaks at 778.2 and 129.1 eV for Co and P are consistent with the binding energy (BE) of the Co− P bond in CoP. 45,47 The P 2p 1/2 located at 130.3 eV is slightly negatively shifted compared to the BE of P 2p 1/2 (130.4) eV in CoP, which might be ascribed to Mn doping.…”
Section: ■ Results and Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…39,45 The broad peak at 134.0 eV is due to the oxidized P species. 46 The peaks at 778.2 and 129.1 eV for Co and P are consistent with the binding energy (BE) of the Co− P bond in CoP. 45,47 The P 2p 1/2 located at 130.3 eV is slightly negatively shifted compared to the BE of P 2p 1/2 (130.4) eV in CoP, which might be ascribed to Mn doping.…”
Section: ■ Results and Discussionsupporting
confidence: 54%
“…In the Co 2p 3/2 region, two peaks assigned to Co 0 and Co 2+ can be observed at 778.2 and 781.4 eV, respectively. , The peak as appeared at 787.3 eV accounts for cobalt oxide or surface oxidized cobalt . In the Co 2p 1/2 region, other two peaks ascribed to Co 0 and Co 2+ appeared at 791.5 and 797.0 eV, respectively. , The peak at 803.1 eV is a usually observed “satellite” peak in CoP. , For P 2p spectrum (Figure d), the peaks at 129.1 and 130.3 eV are attributed to P 2p 3/2 and P 2p 1/2 , respectively, which are assigned to the metal phosphides formed from reduced phosphorus. , The broad peak at 134.0 eV is due to the oxidized P species . The peaks at 778.2 and 129.1 eV for Co and P are consistent with the binding energy (BE) of the Co–P bond in CoP. , The P 2p 1/2 located at 130.3 eV is slightly negatively shifted compared to the BE of P 2p 1/2 (130.4) eV in CoP, which might be ascribed to Mn doping …”
Section: Resultsmentioning
confidence: 90%
“…The pre-catalysts consisting of etchable species, such as metal-organic frameworks (MOFs), [117] metal phosphide, [118] and molybdate, [119] could easier undergo complete reconstruction under certain reaction conditions. For example, Huang et al revealed the real active species for superior OER activity in the hybrid Ni-MOF@Fe-MOF.…”
Section: Deep Reconstructionmentioning
confidence: 99%
“…Also, there are many environmental concerns including air pollution and global warming caused by combustion. 3,4 Thus, nding sustainable energy sources to replace fossil fuels is vital.…”
Section: Introductionmentioning
confidence: 99%